EVALUATION OF THE DOMINANT PHYSICAL CONDITION OF THE ACEH BESAR FENCING ATHLETES IN 2023 - Irwandi Kamalia; Putri Aditia (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The Aceh Besar Fencing Team is a forum for developing athletes to achieve achievements, especially fencing athletes who live in Aceh Besar. The achievements of the Aceh Besar fencing team's sporting achievements cannot be separated from various factors, one of which is physical condition. This study aims to determine the level of physical condition of ASI Aceh Besar fencing athletes. This research method uses a quantitative approach which is presented in descriptive form. The sampling in this research used a purposive sampling technique. Based on the results of the research carried out, the physical condition profile of the ASI Aceh Besar Male Fencing Athletes was classified as adequate in terms of speed and endurance, only the agility section was in the poor category. On the other hand, the physical condition profile of the ASI Aceh Besar Women's Fencing athletes is classified as poor, this can be seen in the data where the overall speed, agility and endurance tests are in the poor category. It is recommended that athletes can improve their physical condition independently outside of the existing training schedule and that coaches can create supporting programs to improve the athlete's physical condition.